Selected bibliography of works on medieval rural settlement 2022–2023 - Dyer, Christopher; Ford, Andy (Medieval Settlement Research, 2024)
A bibliography of books and articles on British and Irish medieval rural settlement between the fifth and fifteenth centuries, published in 2022 and 2023, with the works of each year separately recorded. Books from continental Europe are included if they are deemed to be pertinent for British or Irish settlement studies. The bibliography is focussed on the Group’s specialism of medieval rural settlement. It includes publications deriving from archaeology, place-names, geography and history. Archaeological work on towns, castles, cemeteries or religious sites, or on artefacts or environmental evidence, are not included, except those explicitly connected to rural settlements.